2017
DOI: 10.1002/tea.21433
|View full text |Cite
|
Sign up to set email alerts
|

Students' environmental NOS views, compassion, intent, and action: Impact of place‐based socioscientific issues instruction

Abstract: Preparing students to achieve the lofty goal of functional scientific literacy entails addressing the normative and non‐normative facets of socioscientific issues (SSI) such as scientific processes, the nature of science (NOS) and diverse sociocultural perspectives. SSI instructional approaches have demonstrated some efficacy for promoting students' NOS views, compassion for others, and decision making. However, extant investigations appear to neglect fully engaging students through authentic SSI in several wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 53 publications
3
75
0
4
Order By: Relevance
“…The environmental behaviors field demonstrates that there is only a .45 correlation between stated pro-environmental intentions and enacted behaviors (Gifford & Nilsson, 2014;Kormos & Gifford, 2014). Similar findings have been Zeidler et al Disciplinary and Interdisciplinary Science Education Research (2019) shown with recent SSI research that showed only 44% of secondary students who claimed they would readily donate money to resolve environmental issues actually did so (Herman, 2018). Reconciling these deficits and learning how people respond to SSI as part of their lived experience should be among the foremost imperatives for SSI research.…”
Section: Ssi and The Importance Of Informal And Placebased Contextssupporting
confidence: 63%
See 4 more Smart Citations
“…The environmental behaviors field demonstrates that there is only a .45 correlation between stated pro-environmental intentions and enacted behaviors (Gifford & Nilsson, 2014;Kormos & Gifford, 2014). Similar findings have been Zeidler et al Disciplinary and Interdisciplinary Science Education Research (2019) shown with recent SSI research that showed only 44% of secondary students who claimed they would readily donate money to resolve environmental issues actually did so (Herman, 2018). Reconciling these deficits and learning how people respond to SSI as part of their lived experience should be among the foremost imperatives for SSI research.…”
Section: Ssi and The Importance Of Informal And Placebased Contextssupporting
confidence: 63%
“…Furthermore, the students' developed significantly higher levels of nuanced and targeted compassion toward people and nature impacted by SSI and a willingness to resolve those SSI. Herman (2018) also showed that the students who, after the place-based SSI instruction, donated their participant incentive to a Yellowstone environmental organization demonstrated significantly higher degrees of contextualized NOS understanding, compassion for others impacted by SSI, and willingness to resolve SSI than their non-donating peers. Thus, this study appeared to be an initial effort in the SSI field to link NOS and affective variables to an enacted decision with concrete experienced sacrifice.…”
Section: Ssi and The Importance Of Informal And Placebased Contextsmentioning
confidence: 89%
See 3 more Smart Citations